Smart Agri-preneurship Dimensions and Farm Productivity - A. J Egwakhe,; Ope Omodanisi,; O. E Ajike, (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Smart agri-preneurship is instigating and shaping the scope and depth of farming in crops and animals rearing. This evolves from huge scientific advancement, implementation of various agribusiness tools, and infusion of technologies for the betterment of farm productivity. This paper probes the effect of smart agri-preneurship dimensions on farm productivity in South-West, Nigeria. Cross sectional survey research design was adopted and 558 agri-preneurs were sampled. A structured questionnaire was adapted and used after its validity and reliability were established. The research instrument was self-administered. The analysis revealed that the dimensions of smart agri-preneurship significantly affected farm productivity (Adj. R2 = 0.671, F(6,551), 190.42, p = 0.000). The nature, level, and direction of individual relative effect differ across the constructs. The study recommends continuous deployment of advanced smart technologies that ensures high farm productivity.